(untitled) (OODBODHAN, 2026)
Starch is a vital food product and a versatile biomaterial employed across various industries, including food, health, textiles, chemicals, and engineering globally. Its adaptability for industrial applications is primarily determined by its functionality and physicochemical properties. Advances in chemistry and biotechnology have led to numerous modifications of starch for diverse uses beyond its natural state. To enhance the biocompatibility, biodegradability, and physical characteristics of starch-based biodegradable polymers, various strategies are essential. This study explores the synthesis and functional applications of starch graft copolymer products derived from corn and tapioca starch. It specifically examines the synthetic techniques and utility assessments of several starch-based grafted materials, including maleic anhydride copolymers, substituted amoxicillin grafts, PMMA-grafted starch copolymers, and modifications of corn and tapioca starch through cationization and sulfonation, among others. The novelty in the current studies lies in the transition of these materials from basic biodegradable fillers to high-performance, stimuli-responsive biomaterials tailored for advanced industrial and medical applications. The key advancements focus on synergistic blending, "green" rapid synthesis, and the development of active, intelligent properties that native starch lacks. The work comprises a review of green synthetic approaches and functional utility assessments of synergistic multi-starch formulations.